Efficacy of Lycopene Extracted from Tomato on Liver Enzymes and Tissues of Animal Model Infected with Acrylamide - Maha K. Hammoud; Muhammad J. Muhammad (Journal of Global Innovations in Agricultural Sciences)
Lycopene is a carotenoid derivative, which is a natural pigment synthesized by plants and microorganisms during the photosynthesis process. The study aimed to extract lycopene from tomatoes using organic solvents in a ratio of 2:1:1 of hexane, acetone, and ethanol. The amount of lycopene extracted was (4.87 mg/100 g). We notice a decrease in the values of the liver enzymes ALT, ALK, and AST upon oral administration of lycopene to male infected rats compared to with their values when acrylamide is given alone. A change was also noted in the liver tissue after treatment with lycopene compared to the infected group, as there was an improvement in the central vein, lobules, hepatic sinusoids, and Coover cells after they were congested, expanded, and contained bloody bleeding. In conclusion, lycopene as an antioxidant phyto-component, can protect liver against damages caused by acrylamide (or acrylic amide). Tomatoes can be considering as functional vegetable for protecting liver from damages of chemicals such as acrylamide. Keywords: Acrylamide, lycopene extraction, physiological properties, phytocomponent.